An analysis of the essence of Chinese opera and vocal music from the perspective of hermeneutics and reception aesthetics - Jinjing Xiang (Trans/Form/Ação, 2023)
The development of Chinese opera art, in modern times, has greatly changed with the times. Explaining the essence of Chinese opera and vocal music art from the Western modern hermeneutics and reception aesthetics theory is conducive to sorting out the development context and characteristics of Chinese opera in different times. At the same time, providing a systematic analysis method for modern opera and vocal music aesthetics promotes the aesthetic development of the art and contributes to the form innovation and technical refinement of domestic opera and vocal music art. The research starts with the theoretical analysis of hermeneutics and reception aesthetics and verifies and explores the development history of Chinese opera. The analysis of the artistic essence of opera and vocal music will be summarized mainly from the perspective of the object of the opera text and the subject of the aesthetic audience. The purpose of this research is to explain the essential characteristics of opera and vocal music art from the relationship between the subject and the object. Besides, it aims to examine the relationship between the understanding behavior of the masses and the creators and performers’ summary behavior for opera and vocal music art.